If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -3) = 2y + 3y Reorder the terms: 5(-3 + y) = 2y + 3y (-3 * 5 + y * 5) = 2y + 3y (-15 + 5y) = 2y + 3y Combine like terms: 2y + 3y = 5y -15 + 5y = 5y Add '-5y' to each side of the equation. -15 + 5y + -5y = 5y + -5y Combine like terms: 5y + -5y = 0 -15 + 0 = 5y + -5y -15 = 5y + -5y Combine like terms: 5y + -5y = 0 -15 = 0 Solving -15 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4x-(x-5)=20 | | 8x-20=180 | | 0.07y-0.5=0.34 | | 4x-118=983+x | | 2asqured=56 | | 2a=56 | | 5x-4y=-20*3 | | 7-(-6m)=19 | | 8n+5-4n=-15 | | 43+x+15=3x | | 28(z-1)=3oz | | 6x^2=7y+12 | | 42+2x-38=180 | | 10x^2+14x+24=6x^2+12 | | 0.3(5y-7)-0.2(3y+4)=0 | | Q+32=2q-20 | | 102-4p=-10+3p | | 4x-(3y+5)=-2 | | 4x+4=4(x+1) | | 4x-2=4x-5+3 | | U-8=2u-72 | | 2p=p+50 | | -13+2x-14+3x=3-4x-6-3x | | 240000=X*1.11 | | 6x+6(5-7x)=12 | | -10+3p=24-4p | | (3b+5)=92 | | 2v=v+42 | | -10+3p=102-4p | | 9=2a+3.3 | | 3(x-4)+2x=8+3x | | -5x+(-5x)+(-5x)= |